2013
DOI: 10.1172/jci69404
|View full text |Cite
|
Sign up to set email alerts
|

Melanocyte-secreted fibromodulin promotes an angiogenic microenvironment

Abstract: Studies have established that pigmentation can provide strong, protective effects against certain human diseases. For example, angiogenesis-dependent diseases such as wet age-related macular degeneration and infantile hemangioma are more common in light-skinned individuals of mixed European descent than in AfricanAmericans. Here we found that melanocytes from light-skinned humans and albino mice secrete high levels of fibromodulin (FMOD), which we determined to be a potent angiogenic factor. FMOD treatment sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 46 publications
(41 reference statements)
4
90
1
Order By: Relevance
“…Angiogenesis in vitro as well as in vivo is promoted by fibromodulin, whereas an inhibitory effect has been reported for lumican. [32][33][34][35][36] The connection between diabetes and CV disease is well-documented. [37][38][39] Metabolic abnormalities such as chronic hyperglycemia, dyslipidemia and insulin resistance render arteries more susceptible to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis in vitro as well as in vivo is promoted by fibromodulin, whereas an inhibitory effect has been reported for lumican. [32][33][34][35][36] The connection between diabetes and CV disease is well-documented. [37][38][39] Metabolic abnormalities such as chronic hyperglycemia, dyslipidemia and insulin resistance render arteries more susceptible to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF and ANG2 activate their cognate endothelial receptor tyrosine kinases, VEGFR-2 and TIE2, to induce angiogenic cellular responses. ment with an inhibitory TGF-β antibody (5). Exogenous FMOD induced expression of TGF-βRII, SMAD1, and SMAD5 in ECs, implying an autocrine loop in which FMOD upregulates TGF-β and its receptor, leading to activation of TGF-β signaling and vascular growth (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…In order to identify the specific factor or factors responsible for the observed effects, the authors performed a targeted microarray that compared expression of genes predicted to encode secreted proteins in pigmented and nonpigmented melanocytes (5). Fibromodulin (FMOD), an ECM protein of the small leucine-rich proteoglycan (SLRP) family, was expressed to a much greater degree in nonpigmented melanocytes both in vitro and in vivo.…”
Section: Fibromodulin: a Potent Angiogenic Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, it was suggested that cutaneous vasculature plays a role in regulating skin pigmentation and perhaps its dysfunction in pigmentary diseases [4,5]. Conversely, a regulatory function of melanocytes on vascularization was also discovered, suggesting paracrine crosstalk between endothelial cells and melanocytes [6]. Endothelial cells produce prostaglandins, nitric oxide or endothelin-1 for pigmentation regulation [7].…”
mentioning
confidence: 99%